Towards improving consumer access to justice in Nigeria: assessing the role of small claims court and the legal aid scheme / Dahiru Jafaru Usman, Nurli Yaacob and Aspalella A. Rahman - Usman, Dahiru Jafaru; Yaacob, Nurli; A. Rahman, Aspalella (2014)
This paper examines consumer access to justice from human rights perspective through the prism of international instruments and best practices. The paper found that although access to justice is a global problem, but the Nigerian situation is more worrisome. The Nigerian judicial system is congested and delays prone. The country lacks functional, accessible and expeditious redress mechanisms; and legal aid structures for better consumer access justice. The paper concludes that there is need to overhaul the existing legal and institutional structures in Nigeria to make justice accessible to the Nigerian consumer. The paper recommends the rejuvenation of the extant legal and institutional structures such as the Legal Aid Council and the establishment of small claims/consumer court for better consumer access to justice, and overall consumer rights protection.